Reproductive Health Education and Bullying Prevention - Amelia, Dessy; Merawati, Desiana; Hasanah, Zumroh; Puriastuti, Alifia Candra; Novembriani, Rizqie Putri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescence is crucial for developing knowledge and behaviours related to reproductive health. Bullying in schools is a widespread issue that significantly impacts the mental health and overall well-being of adolescents. School-based health education enhances students' understanding of reproductive health topics. This study aims to assess the understanding of junior high school students in Malang Regency regarding reproductive health education and bullying prevention within schools. Respondents in this study amounted to 814 students who used purposive sampling techniques in sampling research. Using a quantitative approach with a cross-sectional study design, this research analyses the relationship between students' ages and their knowledge of reproductive health and bullying prevention. A questionnaire was administered as the research instrument from July to August 2024. Age plays a significant role in the effectiveness of reproductive health education, as younger adolescents typically possess less knowledge than their older peers. Additionally, the prevalence of bullying tends to decrease with age, particularly among older adolescents. The effects of bullying on mental health also vary based on age and gender. Cultural factors significantly influence adolescents' experiences with reproductive health. The study finds a notable relationship between age and knowledge of reproductive health, as well as awareness of bodily changes and reproductive health issues among junior high school students in Malang Regency.